(untitled) (Current Problems in Rail Vehicles, 2025)
The paper deals with the design of a sensor system for the detection of angle of attack of wheelsets relative to the track. The goal is to develop a contactless, vehicle-mounted method of measuring the angle of attack of wheelsets applicable in tests according to EN14363 and potentially also on vehicles in real operation as part of active radial wheel steering systems. The paper focuses on selection the appropriate type of sensors and their placement, as well as the results of testing in laboratory conditions.